2006
DOI: 10.1120/jacmp.v7i4.2240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contrast‐enhanced CT scans on heterogeneity corrected dose computations in the lung

Abstract: The aim of this study was to investigate and, if possible, compensate for the effect of intravenous contrast‐enhanced CT scans on the treatment planning dose distributions for lung patients. The contrast and noncontrast CT scans of 3 patients were registered, and the effect of contrast on the Hounsfield units (HU) was assessed. The effect of contrast was then simulated in the CT scans of 18 patients receiving radiotherapy of the lung by modification of the CT numbers for relevant sections of noncontrast‐enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…33,34 An additional difficulty concerning this method is that even a slight disturbance in the contrast administration protocol or in the anatomy of the patient may significantly change the image of the scanned structures, which can cause an unwarranted increase in the planned radiation dose when administering radiation therapy. 35,36 In this study we have shown that the XRA values are significantly higher in I-LN compared with NI-LN according to standard criteria. This difference is observed both in the baseline study and after 2 cycles of CTx.…”
Section: Discussionmentioning
confidence: 53%
“…33,34 An additional difficulty concerning this method is that even a slight disturbance in the contrast administration protocol or in the anatomy of the patient may significantly change the image of the scanned structures, which can cause an unwarranted increase in the planned radiation dose when administering radiation therapy. 35,36 In this study we have shown that the XRA values are significantly higher in I-LN compared with NI-LN according to standard criteria. This difference is observed both in the baseline study and after 2 cycles of CTx.…”
Section: Discussionmentioning
confidence: 53%
“…Virtual or arti icial intelligence-based technology methods to reduce dose disturbances in tumour regions (e.g., the lower oesophagus) and thus remove the enhancement effect are also needed (7) . Simple methods (14,15) that incorporate density correction could be applied for clinical corrected dose calculations. for example, the HU values of the heart and great vessels in the enhanced CT were replaced by average HU values obtained from the unenhanced CT, and in the Lung patients the CT to density conversion table used clinically was altered to reduce the effect of the increased density due to the contrast agent, in which tissues with a density between 1 g·cm -3 and 1.2 g·cm -3 were set equal to a density of 1 g·cm -3 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown minimal change in doses mostly below 5% between contrast and non-contrast plans. [20][21][22][23][24] Unfortunately, comparisons are difficult as most studies refer to phantoms and other sites.…”
Section: Rectal Contrastmentioning
confidence: 99%